Penetrasi Politik Identitas melalui Media Sosial: Studi Terbentuknya Identitas Politik “Kampret” dan “Cebong” di Indonesia - Ahmad Irfan Fauzi (Universitas Brawijaya, 2022)
This research discusses the emergence of cebong and kampret political identities and their penetration through social media from 2014 to 2022. Segmentation and doctrine of political groups in the 2014 Presidential Election (Pilpres) clashed where Joko Widodo supporters were labeled as cebong and Prabowo Subianto's supporters as kampret. This is qualitative research. Source of data taken through observation and literature study. The results of the study show that the penetration of cebong and kampret identity politics on social media was formed from clashes between the political elites of the PDI-P Party and the Gerindra Party. The process of defining identity antagonistically by defining who is friend and who is foe participates in strengthening identity which results in a “zero sum game” relationship between subjects. This process triggers the emergence of other definitions of identity such as the kampret label giving rise to the cebong label, the cebong label gives rise to the kadrun label and so on. The next stage of penetration is the emergence of the existence and influence of influencers on the cebong-kapret feud phenomenon. The existence of Ade Armando and Denny Siregar as supporters of Joko Widodo as well as the existence of the Opposite6890 account which created negative narratives against Jokowi's government strengthened this institutionalized polarization. This is also an attempt to impress the existence of enemies that hinder the search for power. The characteristics of social media that provide space for freedom of expression without space and time barriers make political expression negative. The emergence of this political identity group has been identified to trigger the development of blasphemy, hate speech, and hoaxes that have the potential to cause division and undermine the nationalism of Indonesian citizens.